The Ibn Sina Perspective on Education Concept - Minten Apriani; Syahidin Syahidin (Perhimpunan Intelektual Muslim Indonesia, 2021)
In essence, education wants students besides they have extensive knowledge, they also have noble morals and have skills based on their interests. Of the many figures of Islamic education, this study will focus more on Ibn Sina’s thoughts on education. This study aims to identify education from Ibn Sina’s perspective, especially concerning ideal teachers. The research also is expected to give an alternative solution to all kinds of problems in the education world. This research uses a qualitative approach with a library research method. The data collection technique in this research is based on the information contained in literature sources, both in books and journals relevant to the research theme. The journals used in this study amounted to twenty-one journals from 2014 to 2020. At the same time, the books used in this study amounted to two books spanning 2015 to 2017. The research results indicate that Ibn Sina’s thoughts on the concept of education emphasize the achievement of a perfect human. According to Ibn Sina, there are four main points of educational thought, including educational goals, curriculum concepts, learning methods, and educator concepts. These concepts are still very relevant to current education. Based on this, according to Ibn Sina, the concept of education should be emulated and developed by education practitioners in modern times, especially in the development of Islamic education in Indonesia.